Computer-Aided Design Methods in Virtual Reality Product Development - Shan Guan (Advances in Multimedia)
In order to improve the effectiveness of virtual reality product design, this paper combines the computer-aided design method to construct a virtual reality product development system and analyzes the elements, architecture, and calculation steps of the virtual reality model in detail. Moreover, from the research on the color appearance phenomenon, this paper leads to the improvement direction of improving the virtual reality model. In addition, this paper discusses the advantages of the virtual reality product design model and its feasibility as a PCS link space to undertake the task of color appearance transformation. The experimental research analysis shows that the virtual reality product design system based on computer-aided technology proposed in this paper has good effects and can effectively improve the effect of virtual reality product design.